2021
DOI: 10.1039/d1ra05041a
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer based surface plasma resonance assay for direct detection of neuron specific enolase and progastrin-releasing peptide (31-98)

Abstract: Direct detection of neuron specific enolase and progastrin-releasing peptide (31-98) were achieved by measuring the target-induced SPR response of an aptamer-coated chip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The change in the SPR signal was used to quantify the ProGRP in the sample. The LOD of the proposed system was calculated to be 15.6 nM [ 105 ]. Wang et al reported a molecularly imprinted photoelectrochemical sensor for the sensitive detection of ProGRP lung cancer biomarkers.…”
Section: Biomarkers and Their Biosensorsmentioning
confidence: 99%
“…The change in the SPR signal was used to quantify the ProGRP in the sample. The LOD of the proposed system was calculated to be 15.6 nM [ 105 ]. Wang et al reported a molecularly imprinted photoelectrochemical sensor for the sensitive detection of ProGRP lung cancer biomarkers.…”
Section: Biomarkers and Their Biosensorsmentioning
confidence: 99%
“…21 Therefore, the NSE is one of the important biomarkers to be monitored. 22 Detection of NSE has been reported using various biosensing schemes, including surface plasmon resonance (SPR) spectroscopy, 23 surface plasmon-enhanced uorescence (SPF), 24,25 uorescence, 26 electrochemistry, [27][28][29] and photoelectrochemistry. 30,31 Nevertheless, most of the sensing methods rely on the development of nanomaterials that enhance or produce the sensor signals to detect NSE at its clinical threshold value.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of NSE in serum rises significantly in patients with small cell lung cancer, neuroblastoma, or chemotherapy. As a tumor marker with high specificity, the rapid and reliable detection of NSE is critical for illness diagnosis and timely detection of diagnosis and treatment outcomes. , In this study, homogeneous and dense TiO 2 nanorod films were produced in situ on the surface of FTO and TiO 2 was sensitized by CdS. The TiO 2 /CdS composite materials can help to separate electrons and holes and increase visible light utilization.…”
Section: Introductionmentioning
confidence: 99%